IDEAS PROMOTED BY DMYTRO OVSIANYKO-KULIKOVSKYI WITHIN THE CONTEXT OF THE DEVELOPMENT OF THE UKRAINIAN PSYCHOLONQUISTICS - Papish, Vitalija (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction: D. Ovsianyko-Kulykovskyi is considered the iconic figure of the Ukrainian science, significant representative of the Kharkiv psyholonquistic school, disciple and follower of the Potebnia’s theory. For the reason that mostly his works were published in Russian language his personality has evinced less interests of the modern scientists, however due attention is to be given to his ideas within the system of modern sciences the part whereof is psycholinguistics. Purpose: The main subject of this scientific article is to draw attention to the pivotal provisions of the scientific concept of D. Ovsianyko-Kulykovskyi, to generalize scientific material he accumulated and demonstrate how his psycholinguistic ideas are re- interpreted and promoted nowadays. The subject of observation is the system of idea on psychological phenomena by D. Ovsianyko-Kulykovskyi what may be considered principal for modern Ukrainian psycholinguistics. Results: The article contains analysis the outstanding contribution made by D. Ovsianyko-Kulykovskyi to the development of the Ukrainian psycholinguistics. Some his ideas are actualized such as provisions of his psycholinguistics theory focused on the psychology of human giftedness, role of irrational aspect for text creation, psychological nature of a word, psychological interpretation of a text, associative – imperceptive processes, psychology of ethnicity. Special attention is paid to the problems he dealt with as the interrelation of psychic and artistic vision of the world by an artist, role of artistic intuition. It is found out that working on the subject of displaying norms and pathologies in the language the Ukrainian scientist “came closer” to the notion of the accentuated language, particularly to the ideas of psychoaccentuation. Herein given characteristics of the instruments of psychological interpretation of the linguistic phenomena, in particular, psycholinguistics methods, applied by the science: it is mostly experiment and observation. D.Ovsianyko-Kulykovskyi is represented as promoter of the ideas by O. Potebnia on the psychological nature of the language owning to development of the theory of emotional and creative nature of the language. The reasons given why the creative heritage of the Ukrainian scientist has been out of attention and given names of his contemporaries who highly appreciated his scientific input. Originality. The article presents systematization of psychological ideas of D. Ovsianyko-Kulykovskyi, which theretofore have not been clearly outlined or analized as ingredient of other ideas. His ideas are relevant nowdays and significant for evolvement of the Ukrainian psycholinquistics. Conclusions and specific suggestions of the author. Dmytro Ovsianiko-Kulikovsky concept is worth and due to be promoted. The prospects for studies are conditioned by the fact that it is necessary to terminate blank gaps in the history of the national psycholonquistics by incorporating in the Ukrainian historiography postulates of the theory by Dmytro Ovsianyko-Kulykovskyi.